1999
DOI: 10.1017/s0022112099006473
|View full text |Cite
|
Sign up to set email alerts
|

Development and stability of gyrotactic plumes in bioconvection

Abstract: Using the continuum model of Pedley, Hill & Kessler (1988) for bioconvection in a suspension of swimming, gyrotactic micro-organisms, we investigate the existence and stability of a two-dimensional plume in tall, narrow chambers with stress-free sidewalls. The system is governed by the Navier-Stokes equations for an incompressible fluid coupled with a micro-organism conservation equation. These equations are solved numerically using a conservative finite-difference scheme. In sufficiently deep chambers, the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 28 publications
4
87
0
Order By: Relevance
“…To validate the code, written in terms of stretched coordinates, the code has been run for the heat convection problem and the agreement with the benchmark solution of De Vahl Davis (1983) (Ghorai, 1997) is good. The code has also been used to compute the critical Rayleigh numbers against wavelengths (Ghorai and Hill, 1999) and the agreement with the linear stability results of Hill et al (1989) is excellent.…”
Section: Numerical Proceduresmentioning
confidence: 88%
See 1 more Smart Citation
“…To validate the code, written in terms of stretched coordinates, the code has been run for the heat convection problem and the agreement with the benchmark solution of De Vahl Davis (1983) (Ghorai, 1997) is good. The code has also been used to compute the critical Rayleigh numbers against wavelengths (Ghorai and Hill, 1999) and the agreement with the linear stability results of Hill et al (1989) is excellent.…”
Section: Numerical Proceduresmentioning
confidence: 88%
“…If the vorticity is large ( |Bζ | > 1), the cell tumbles but swims on average in a fixed direction at an angle to the vertical (Kessler, 1985b). When the vorticity is large, the average swimming directionp is approximated by integrating the swimming direction over the tumbling period (Ghorai and Hill, 1999).…”
Section: Governing Equations As Inmentioning
confidence: 99%
“…Although this configuration is not exactly the same as that of the experiment by Kessler (1985a) and Kessler (1986), we will see that many features of the instability found in the present study are remarkably similar to the blips observed in the pipe experiment. Finally, we should emphasise that the present study should be distinguished from previous work by Ghorai & Hill (1999, 2000 who performed a linear stability analysis of naturally arising 'standing' gyrotactic plumes. In the present study, the basic state, obtained in the form of the beam-like structure as in the experiment, is essentially caused by the imposed flow.…”
Section: Introductionmentioning
confidence: 89%
“…Although the role of this mechanism has not been discussed at all, the related term does appear e.g. in the equations of Ghorai & Hill (1999). We note that this mechanism is represented by the term D⟨e 2 ⟩ 0n in (2.21e), which describes production due to the gradient in the cell swimming vector field.…”
Section: Physical Mechanisms Of the Instabilities: Budget Analysismentioning
confidence: 99%
See 1 more Smart Citation